Innovative Insurance to Manage Climate Risks - Miller, Alan; Swann, Stacy (International Finance Corporation, Washington, DC, 2018)
Severe storms, record heat waves, intense droughts, and floods—the impact of climate change rises every year and economic and financial losses rise with it. Insurance plays a major role in helping businesses in advanced economies mitigate the consequences of the changing climate and prepare for policy changes ahead. But insurance in emerging markets isn’t yet able to make the same contribution, despite the fact that natural disasters disproportionally affect people and firms in these countries. Recently, however, a number of new business and donor initiatives have begun to create innovative approaches to using insurance to address climate change.